Case Report: Personalized treatment in stage IV breast cancer using the patient-derived organoids - Ying, Wu; Pi, Hao; He, Xiaowu; Sheng, Yuan (Frontiers in Oncology, 2025)
Breast cancer, especially stage IV breast cancer, is highly heterogeneous at morphological and molecular levels. Recently, the role of patient-derived organoids (PDOs) has become increasingly prominent in cancer research and personalized medicine. They are not only used to predict the clinical responses of patients with multiple cancer types, but also applied to drug development. In this study, we reported a case of stage IV breast cancer who responded well to sacituzumab govitecan that was highly sensitive by the PDO-based drug sensitivity testing, good pathological response was obtained postoperatively. This typical case suggests that PDO-based drug sensitivity testing is conductive to tailoring neoadjuvant chemotherapy options to enhance the feasibility of surgical resection in patients with stage IV breast cancer, thus improving the prognosis.